ANALISIS KEBUTUHAN DAN KETERSEDIAAN AIR BERSIH DI KECAMATAN KLEGO KABUPATEN BOYOLALI - Leksana, Rudi; Rizani, Mohammad Debby; Ikhwanudin, ikhwanudin; Aksin, Nur (Jurnal Teknik Sipil Giratory UPGRIS, 2024)
Clean water is one of important needs for human in their daily life. According to Central Statistic Department of Boyolali in 2018 TO 2021, the population of society in Klego District increased in 2022. It caused the clean water needs also increased. The services of infrastructure and clean water availability was not maximal yet causes the society must to look for the alternative sources of clean water to fulfill their clean water needs. The purposes of this research are to know the water needs and water ability and to know the reservoir capacity to be accomodate of the clean water. This research contains aboot the water needs and availability in Klego, Boyolali District. The researcher start the research by secondary data collection such as population data, the customer data, source capacity data and clean water production discharge data. In the calculation of society population, the researcher used population data in last 5 years with calculation prediction until 2032. To calculate the data, the researchers used Geometry method, Arithmetic method, and Linier Regression method. Then from the calculation, the researcher choose Arithmethic method because it have the smaller values. According to the calculation of the data by using Arithmetic method, so it is obtained the number of clean water needs, there is 66,69 liter/second in 2032 from the calculation of society population data, beside that, the clean water needs, there is 0,67 liter/second in 2032 from PDAM's customer calculation. The clean water availability, there are 10 liter/second for source capacity and 1,9 liter/second for the production discharge in 2031. Then, the reservoir capacity is 15, 482 m3.